The Influence of Knowledge, Attitude, and Motivation on Patient Identification Compliance - Ichsan Nur Hamdan; Yanuar Jak; Santi Anugrahsari (Indonesian Journal of Global Health Research, 2026)
Patient safety is a priority in improving the quality of healthcare services, with patient identification serving as a critical initial step to prevent medical errors. RSUD Sungai Lilin reported 100% compliance with patient identification; however, observations indicated that practices were not consistently implemented. This study aimed to analyse the influence of knowledge, attitude, and motivation on staff compliance with patient identification procedures at RSUD Sungai Lilin, Musi Banyuasin Regency, in 2025. A quantitative design was employed using an observational analytic survey with a cross-sectional approach. Data were collected through questionnaires using a total sampling method involving 186 healthcare providers directly delivering patient care, as well as secondary data from the administrative department. The validity test results showed that all questionnaire items had r-values greater than the r-table value of 0.301 and Cronbach’s Alpha values greater than 0.6. The analysis assessed the relationship between the independent variables (knowledge, attitude, motivation) and the dependent variable (compliance with patient identification). The findings revealed that most personnel possessed good knowledge, demonstrated positive attitudes, and exhibited supportive work motivation. Compliance was generally high, although inconsistencies were observed under certain conditions. Statistical tests indicated significant associations between knowledge (p = 0.020), attitude (p = 0.009), and motivation (p = 0.009) with compliance. Motivation emerged as the dominant factor influencing adherence to patient identification. It is concluded that compliance with patient identification is influenced by knowledge, attitude, and motivation, with motivation representing the primary determinant.